2006
DOI: 10.1103/physrevd.74.123004
|View full text |Cite
|
Sign up to set email alerts
|

Collective neutrino flavor transformation in supernovae

Abstract: We examine coherent active-active channel neutrino flavor evolution in environments where neutrino-neutrino forward scattering can engender large-scale collective flavor transformation. We introduce the concept of neutrino flavor isospin which treats neutrinos and antineutrinos on an equal footing, and which facilitates the analysis of neutrino systems in terms of the spin precession analogy. We point out a key quantity, the "total effective energy", which is conserved in several important regimes. Using this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
520
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(529 citation statements)
references
References 27 publications
8
520
0
1
Order By: Relevance
“…This phenomenon is different from the conventional Mikheyev-Smirnov-Wolfenstein (MSW) effect [14,15] in that the flavour evolution histories of neutrinos in collective oscillations are coupled together and must be solved simultaneously. The possibility and consequences of collective neutrino oscillations in supernovae were not well appreciated until the discovery that the ordinary matter can be "ignored" in such phenomena [16] and the first numerical demonstrations of "stepwise spectral swapping" (or "spectral split") [17,18] which is the imprint left by the collective flavour transformation on neutrino energy spectra.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is different from the conventional Mikheyev-Smirnov-Wolfenstein (MSW) effect [14,15] in that the flavour evolution histories of neutrinos in collective oscillations are coupled together and must be solved simultaneously. The possibility and consequences of collective neutrino oscillations in supernovae were not well appreciated until the discovery that the ordinary matter can be "ignored" in such phenomena [16] and the first numerical demonstrations of "stepwise spectral swapping" (or "spectral split") [17,18] which is the imprint left by the collective flavour transformation on neutrino energy spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of neutrino-neutrino over neutrino-electron forward scattering couples flavor evolution of neutrinos that have different energy and travel on different trajectories, thereby giving rise to new phenomena. Assuming no CP-violation in the neutrino sector, [8][9][10] first showed that collective oscillations of supernova neutrinos can occur for the vacuum-mass-squared difference δm 2 13 relevant for atmospheric neutrino oscillations. This collective flavor transformation can be treated effectively as 2 × 2 mixing between ν e and ν x (ν e andν x ), where ν x (ν x ) is a superposition of ν µ and ν τ (ν µ andν τ ), because ν µ and ν τ (ν µ andν τ ) have identical emission characteristics and interactions in supernovae.…”
mentioning
confidence: 99%
“…Subsequent to the study in [10], a number of authors have investigated collective oscillations of supernova neutrinos (see [4] for a review). The most prominent feature of collective oscillations is the stepwise swap of the ν e and ν x energy spectra at some characteristic "split" energy [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous literature it was recognized that a constant matter profile essentially reduces the effective mixing angle so that matter should have the same influence as a small vacuum mixing angle [4,7]. We illustrate this point in Fig.…”
Section: Role Of Model Parameters a Ordinary Mattermentioning
confidence: 65%